Intervention of Post-Menopausal Dry Eye with Shatavari Ghrita: Case study (Asian Journal of Pharmaceutics (AJP), 2025)
Dry eye disease (DED) is a common condition in post-menopausal women, primarily due to hormonal changes,particularly the decline in estrogen. This case report describes the treatment of a post-menopausal womandiagnosed with DED using shatavari, an adaptogenic herb from traditional Ayurvedic medicine. Shatavari grithaeye drops improve the symptoms of dry eye and shatavari ksheerapaka internally improves the menopausalsymptoms. Due to rasayana, vayastapana and madhura rasa and vipaka it helps to reduce vata and pitta doshas.The patient experienced significant improvement in symptoms and quality of life, suggesting that shatavari couldbe a potential therapeutic option for managing post-menopausal dry eye.